Extracellular matrix collagen-I fibrillar networks in bone tissue engineering – analysis with SHG and multiphoton microscopy - Vielreicher, Martin; Detsch, Rainer; Boccaccini, Aldo R.; Friedrich, Oliver (5th International Congress on Stem Cells and Tissue Formation (Deutsche Gesellschaft für Zytometrie, DGfZ), 2014)
Question: Bone Tissue Engineering: Do mesenchymal stem cells (MSC`s) form better and more collagen-I fibers in 3D vs 2D cell culture? Methods: MSC`s isolated from rat femur were tested in 2D (monolayers, biomaterial films) vs. 3D systems (pellet, hydrogel or scaffold cultures) and grown in normal or serum-reduced or in osteogenic medium (1% FBS). Bone tissue-relevant biomaterials were cross-linked alginate-gelatin, collagen-I, PCL and PCL-Bioglass. Cells were imaged with label-free and depthresolved multiphoton microscopy by their autofluorescence or nuclear/membrane stainings. Produced collagen-I fibers were detected using second harmonic generation (SHG) and, as control, immunofluorescence (IF). Parallel collagen-I detection occurred using Western Blotting (WB) after solubilization with pepsin at pH2. Results: WB and IF analysis showed that MSC`s formed collagen-I in both 2D and 3D systems in plain and biomaterial containing constructs. Fibrous collagen susceptible to SHG, however, was detected in monolayers (2D) only after stimulation with osteogenic medium. In contrast, clear and strong fiber networks appeared in cell pellets. Depending on culture media these networks differed largely in their morphology and resembled the appearance in native tissue (Fig. 1). Simultaneous SHG/AF imaging at 810nm enabled detailed imaging and 3D reconstructions of the artificial tissues (cells with surrounding collagen-I). Conclusions: MSC`s require a 3D surrounding and high initial cell density to effectively form thick and stable fibers and fiber networks. These are preferably imaged using SHG which preferably detects larger and highly assembled fibers rather than thin fibrils (Vielreicher et al. 2013. J R Soc Interface, 10(86):20130263). The differentiation state of MSC`s has a large effect on the morphology of the formed collagen networks. The collagen fibers formed in 2D cell culture are not comparably stable, putatively due to less and weaker focal adhesion contacts. Studying collagen fiber and ECM networks in general is of high interest in the engineering of artificial tissue